Analysis on flexural behavior of fabricated steel keel foamed concrete strip. Issue 1 (1st June 2022) - Hong, Cheng; Zhou, Haonan; Liu, Kai; Tu, Bin; Su, Ge
Abstract: The new fabricated steel keel foamed concrete strip wall panel studied in this paper is a new steel-concrete non load-bearing outer wall panel based on the traditional fabricated foamed concrete outer wall panel. The utility model is composed of a built-in crack resistant steel wire mesh, a foamed concrete vertical plate and embedded light steel keels on both sides. When in use, the light steel keels on both sides of the strip wallboard are connected by welding to form a residential enclosure system. In order to study the bending performance of this new wall panel, this paper uses Midas FEA finite element software to carry out three-dimensional modeling of the wall panel, deformation and strain analysis under Z-direction concentrated load, and draw load deflection curve and load strain curve. The results show that under the load, the steel-concrete synergy is obvious and the stress is clear. The light steel keel has a great contribution to the flexural capacity of the wall panel, and the overall flexural performance of the wall panel is excellent.